When and Why Do Buyers Rate in Online Markets? - Xiang Hui; Tobias J. Klein; Konrad O. Stahl (Center for Economic Studies and ifo Institute (CESifo), 2022)
Online ratings play an important role in many markets. We study the often disputed information content of these ratings, by proposing a reduced-form Bayesian model of the typical buyer's rating decision. Our empirical evidence based on eBay raw data is in line with even intricate predictions from it. We thus have good reasons to calibrate the model to moments of the data. Our simulations suggest that the rating record reveals the seller's type after about 100 transactions, or 65-70 ratings.
Keywords: D83; L12; L13; L81; 330; online markets; rating; reputation